Desenvolvimento e validação de metodologia analíticapara quantificação de compostos fenólicos e avaliação da atividade antioxidante e antimicrobianado extrato de Maytenus obtusifolia Mart. (Celastraceae) - Araújo, Diego Igor Alves Fernandes de (2015)
The use of natural products for the treatment of diseases is a traditional practice supported by ethnopharmacology.The species Maytenus obtusifolia Mart (Celastraceae) is popularly known as carne de anta, congonha brava de folha miúda e lenha branca, and is often used for gastric ulcer treatments and as an antiseptic. It presents distribution in coastal regions occurring from the state of Pará to São Paulo. Previous studies of the species reported the presence of pentacyclic triterpenoids, flavonoids and alkaloids in its chemical composition. And the pharmacological studies have demonstrated antimicrobial activity of essential oil and gastroprotective activity and antiulcer for the extract. Thus, the objectives of this paper was to perform quality control of plant material through pharmacopeial trials, to develop and validate analytical methodology for quantification of phenolic compounds in ethanol extract of M. obtusifolia (EEMO), ascertain the photostability of the compounds under study and evaluate the antioxidant and antimicrobial activities from extract. The determination of water in vegetable drugs, determination of total ash and sulphated ash, heavy metals limit test, determination of bulk density solids, total flavonoid content, total tannin and determination of microbiological contamination were evaluated in accordance with the methods described in Brazilian pharmacopoeia 5th edition.The quantification of total phenolic was performed by spectrophotometric method using ascorbic acid as standard. It was observed that the species has a wealth of polyphenolic compounds since there was obtained (134,76 mg GAE / g ± 0,377) in the assay of total phenolic compounds , as well as (17,85%± 0.234) of total tannins, (4,72 ± 0,102 %) of total flavonoids and calculated as apigenin and (6,24% ± 0,064) flavonoids calculated as hyperoside.The analytical method was developed and validated HPLC-PDA for markers (-)-Epigallocatechin (EGC), (+)-Catechin (CAT) and (-)-Epicatechin (EPI) and showed specificity, linearity, precision, intermediate precision, accuracy and robustness in accordance with the specifications required by ANVISA in the Guide to Validation of analytical and bioanalytical methods (RE nº 899/2003).The EEMO showed small variations in the CAT marker content (7,594 %) and its isomer EPI(4,718%) when exposed to visible light, while the concentration of (-)-Epigallocatechin remained unchanged. When assessed under UVA radiation, there was a significant reduction EGC (36,180 %), CAT (17,293 %) and EPI (29,878 %).The antioxidant activity was performed using the indirect method with DPPH radical and presented efficient results (IC50 21,01 ± 1,02 µg/mL), as the standard ascorbic acid (IC50 19,17 ± 2,32 µg/mL) whose use is established as an antioxidant.The evaluation of the antimicrobial activity from EEMO was performed at concentrations from 1024 to 32 µg/mL, using the technique of microdilution in liquid medium against 4 bacterial and 8 fungal strains and it was observed that the concentrations of 1024, 512, 256 and 128 µg/mL showed activity against bacteria and fungi.